"Na krawędzi między dwiema swoimi ojczyznami…" Hiszpańskie rozrachunki poety Marcjalisa - Danek, Zbigniew (Rzym a Półwysep Iberyjski: Inspiracje i powiązania na przestrzeni dziejów, 2021)
This chapter deals with the issue of the motivations that made Martialis, a Spanish native of Bilbilis, decide to leave the capital of the Empire after many years of fruitful residence in Rome and return to his native land. Analysing the references to the Spanish land that can be found in the epigrams of Martialis, it can be assumed that the strongest motivation for this was his memory of his home town, that is of Bilbilis, which certainly dominates over the sentiment to the Spanish land as an ethnic and geographical whole. It should be emphasized, however, that Martialis, who treated both Rome and his home town with a sufficient degree of criticism, in returning to his homeland, was guided not so much by sentiment and emotion, as by the need for inner peace, so desirable for a man who is closing his life balance.